MULTI-VECTOR FOREIGN POLICY OF AZERBAIJAN - Nikolic, Danijela; Talovic, Violeta (Serbian political thought, 2025)
The geopolitical positions of Russia, Iran, and Turkey, combined with significant energy reserves, enabled Azerbaijan to develop a dynamic and flexible foreign policy to preserve its security, territorial integrity, and economic prosperity. The changes and challenges in regional security have been pronounced in the last ten years since the renewal of conflict with Armenia and the deepening of the cooperation with Türkiye and Russia, to maintain stable relations with the West, including the United States of America. As a state positioned at the crossroads of Eurasian forces, with resources of strategic significance (oil and gas), Azerbaijan is following a multi-vector foreign policy to balance the influences of Russia, Türkiye, Iran, the United States of America (USA), and the West in a broader sense. The paper focuses on relations with key regional and global actors, with a special emphasis on the long-standing conflict with Armenia in Nagorno-Karabakh, the growing cooperation with Türkiye, diplomatic maneuvering in the relations with Russia and Iran, as well as a limited, but still significant influence of the USA. This paper aims to analyze the security and geopolitical aspects of the multi-vector foreign policy of Azerbaijan in the period from 2014 to 2024. In terms of methodology, the research rests on the analysis of secondary sources, comparative analysis of regional relations, a case study (Nagorno-Karabakh), as well as the analysis of political statements, official documents, and security indicators. The paper uses a realistic theoretical framework in which states act based on national interests in the system of anarchy and the constant fight for power and influence.